'Moralising' Welfare and migration in austerity Britain: a backdrop to Brexit. Issue 1 (1st January 2019) - Morris, L. D.
ABSTRACT: This article begins by examining UK government discourse on welfare and migration for the period 2010–2016, viewed here as the expression of a distinctive process of moralisation. This discourse is characterised by claims to fairness, responsibility, and austerity, and explicitly sets domestic welfare dependency and migration in opposition to each other. Its operationalisation is traced through a formal mapping of civic stratification in relation to both domestic welfare and freedom of movement within the European Union, while also noting the absence of supporting empirical evidence. The article then looks to the informal aspect of civic stratification, and the role of political discourse in negatively shaping the moral standing of both domestic welfare recipients and EU migrants. Together with the uneven impact of welfare reform, their discursive opposition provides an important amplification of common understandings of the Brexit vote as delivered by the 'left behind' (Goodwin, M. and Heath, D. (2016) 'The 2016 Referendum, Brexit and the Left Behind', The Political Quarterly 87(3): 323–332).